2013
DOI: 10.1371/journal.pone.0063956
|View full text |Cite
|
Sign up to set email alerts
|

Biological N2O Fixation in the Eastern South Pacific Ocean and Marine Cyanobacterial Cultures

Abstract: Despite the importance of nitrous oxide (N2O) in the global radiative balance and atmospheric ozone chemistry, its sources and sinks within the Earth’s system are still poorly understood. In the ocean, N2O is produced by microbiological processes such as nitrification and partial denitrification, which account for about a third of global emissions. Conversely, complete denitrification (the dissimilative reduction of N2O to N2) under suboxic/anoxic conditions is the only known pathway accountable for N2O consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 68 publications
1
51
1
Order By: Relevance
“…The 15 N-N 2 experiments were also positive at most of the sampling stations, indicating new input of N into the system, which may support the hypothesis that N 2 fixation is an extremely versatile process, being led by both autotrophic (Cyanobacteria) and heterotrophic bacteria in Arctic Ocean brine and seawater. Thus, the existence of N-fixing microorganisms in this marine region may have an effect on the N 2 O inventory, which could be used as an alternative substrate, as suggested by Farías et al (2013). Microorganisms that carry out biological N 2 O fixation could produce N 2 O depletion and simultaneous under-saturation in these marine environments.…”
Section: Pml and Haloclinementioning
confidence: 93%
“…The 15 N-N 2 experiments were also positive at most of the sampling stations, indicating new input of N into the system, which may support the hypothesis that N 2 fixation is an extremely versatile process, being led by both autotrophic (Cyanobacteria) and heterotrophic bacteria in Arctic Ocean brine and seawater. Thus, the existence of N-fixing microorganisms in this marine region may have an effect on the N 2 O inventory, which could be used as an alternative substrate, as suggested by Farías et al (2013). Microorganisms that carry out biological N 2 O fixation could produce N 2 O depletion and simultaneous under-saturation in these marine environments.…”
Section: Pml and Haloclinementioning
confidence: 93%
“…Chlorophyll and CDOM exhibit very tightly coupled seasonal co-variations, suggesting that seasonal variations in sea surface chlorophyll might not reflect true Farías, et al (2013). biomass variations. Instead variations in the depth of the mixed layer and level of mixing might cause more unbleached CDOM and higher pigmented cells to be transported towards the surface in the winter, whereas cells and CDOM near the surface in the summer have been exposed to solar bleaching for longer on average (Morel et al, 2010).…”
Section: Pelagic Biogeochemistry Of the South Pacific Subtropical Gyrmentioning
confidence: 99%
“…This suggests that there is a close relationship between phytoplankton, the only producers of DMSP (Yoch, 2002), and microbial communities which may be recycling DMS. Phyto-and bacterioplankton relationships control DMS turnover, which could result in several mechanisms of DMSP/DMS degradation (Simó et al, 2002;VilaCosta et al, 2006) and produce CH 4 (Damm et al, 2010;Florez-Leiva et al, 2013;Weller et al, 2013). These publications show that phytoplankton species composition and biomass in different bloom phases, as well as eddy dynamics, were important determinants of CH 4 saturation and emission.…”
Section: Ch 4 Cyclingmentioning
confidence: 99%
“…Christaki et al (2014) showed that the highest bacterial production rates (up to 110 mg C m −2 d −1 ) and the greatest abundance of heterotrophic bacteria were associated with stations where the phytoplankton bloom was developed (TEW-7 and A3-2). Recent evidence indicates that methylotrophs are candidates for mediated CH 4 generation using methylated compounds such as DMSP and DMS (Florez-Leiva et al, 2013;Weller et al, 2013). Among these heterotrophic microorganisms DMS degradation can be ascribed to methylotrophic bacteria (Vissher et al, 1994) that derive energy from the conversion of methyl into other products, as well as using S as a source of methionine biosynthesis (Kiene et al, 1999).…”
Section: Ch 4 Cyclingmentioning
confidence: 99%
See 1 more Smart Citation